APLIKASI PENGECEKAN STOK DAN PEMESANAN GAS LPG 3 KG MENGGUNAKAN NOMOR KTP BERBASIS PERHITUNGAN MATEMATIKA DASAR - Supu, Nur 'Ain; Pakaya, Nahdalia (Jurnal Technopreneur (JTech), 2025)
LPG 3 kg gas is a primary energy source for households in Indonesia, making accurate stock management and distribution control essential. Common problems at the distribution level include inaccurate stock records, irregular ordering, and inefficient manual data processing. This study aims to design and develop a web-based application for checking stock and ordering LPG 3 kg gas using the national ID number (KTP) as a unique customer identifier, integrated with basic mathematical calculations. The application applies basic arithmetic operations to calculate incoming stock, outgoing stock, and remaining stock, as well as percentage and average calculations as part of descriptive statistics. Data were collected through interviews and documentation at several gas distribution points in Sumalata Timur District. The results show that the developed application improves stock data accuracy, simplifies the ordering process, and supports real-time monitoring of LPG availability. The implementation of basic mathematical calculations also assists decision-making and enhances the efficiency of LPG 3 kg gas distribution.